Classifying physical activity research following stroke using the behavioral epidemiologic framework. Issue 4 (August 2015) - Cleveland, Samantha; Driver, Simon; Swank, Chad; Macklin, Staci
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Stroke is a significant public health issue in the USA and a need emerges to better understand how to reduce an individual's co-morbidity risk. Physical activity is one approach to improving the health of individuals and comprehensive literature supports increased activity as a means to reduce risk of morbidity and mortality. One approach to examining whether research in a field is addressing a public health issue is through application of the behavioral epidemiological framework. Objective: To classify physical activity research for individuals following stroke into distinct phases so that efforts can be made to systematically address gaps and disseminate evidence-based practice. Methods: Specific key words were identified and then searched through EBSCOhost, PubMed, and Google Scholar. Physical activity and stroke literature from 2000–2014 was categorized into one of five discrete phases. Research in Phase 1 identified associations between activity and health; Phase 2 established valid measures of activity; Phase 3 examined determinants of behavior; Phase 4 evaluated activity interventions; and Phase 5 disseminated evidence-based practice. Results: A comprehensive review of literature identified 202 articles with 70% categorized in Phase 1 (n = 141), 11% in Phase 2 (n = 23), 10% in Phase 3 (n = 20), 8% in Phase 4 (n = 15), and 1% in Phase 5 (n = 3). Conclusion: Findings suggest that physical activity research for individuals following stroke is in the early stages of development with less than 10% of research evaluating or disseminating interventions.